Smart system that facilitates the learning process of bird identification via image scanning. - García-Arias, Sabrina (2023)
Birdwatching tourism in Costa Rica has increased in recent years, with national and international tourists traveling from many places solely to engage in this activity. However, there are still promotion challenges, as there is a common belief that only people with prior knowledge can partake in it, causing interested individuals to lose motivation and refrain from taking the plunge into birdwatching. To address this issue and welcome new enthusiasts to birdwatching, an innovative solution based on Design Thinking methodology was conceived, resulting in the creation of Batsù, an intelligent device aimed at breaking down the barriers that hinder learning and bird identification during observation activities. Its development aims to encourage new users to immerse themselves in the world of birdwatching, boost the country's tourism sector, and promote the learning and conservation of Costa Rica's rich ornithological heritage. Thus, Batsù represents a significant advancement in birdwatching promotion by facilitating access and participation for new enthusiasts, contributing to the sustainable tourism development in the country, and strengthening environmental awareness.